PELAKSANAAN PENGELOLAAN SAMPAH OLEH PEMERINTAH KOTA PEKANBARU TAHUN 2018 - Milandry, Alkausari Trinandika; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Pekanbaru city plays a role as the center of government, education, industry and trade. It increases the population extremely. This is one of the triggers of increasing the amount and complexity of waste.  In order to minimalize the amount of waste, some of terms have done by waste bank and compost houses. Waste management is one of the authorities of City Environment and Sanitation Service Department of Pekanbaru. It aims to cover the solid waste problem by increasing, encouraging and facilitating the provision of facilities and infrastructure, as well as growing public awareness in waste management. However, there are some sources pertinent to the waste management. They are the unable infrastructure and facilities, lack of the public awareness and the less strictness of both Regional and Mayor Regulations and Circular on waste management.The recent research aimed to identify the implementation of waste management by the government of Pekanbaru in 2018 by using descriptive qualitative method. Furthermore, the data were collected by using documentation and interview. They were analyzed by collecting the information, data reduction, and data presentation. Additionally, the theory of policy implementation was applied.The result found that the implementation of waste management by the Pekanbaru Government in 2018 has not been running optimally. The lack of facilities, supervision of the government and socialization of the regulation have resulted the waste problem hard to solve. Keyword: Waste management, policy implementation